Impact of Online Racism on Suicide Ideation Through Interpersonal Factors Among Racial Minority Emerging Adults: The Role of Perceived Burdensomeness and Thwarted Belongingness - Keum, Brian TaeHyuk (Journal of interpersonal violence, 2023)
While a growing number of studies have documented significant links between online racism (e.g., racist interactions, contents on racial violence) and comorbid factors (e.g., depression) associated with suicide risk, no studies have examined whether online racism predicts suicide ideation and if interpersonal factors can help explain this link. Thus, the current study examined the direct relationship between online racism and suicide ideation among racial minority emerging adults, and the indirect relationships via the interpersonal factors (perceived burdensomeness and thwarted belongingness). Using data from a convenience sample of 338 racial minority emerging adults, we conducted a path analysis with online racism predicting suicide ideation through thwarted belongingness and perceived burdensomeness. Online racism significantly predicted suicide ideation via perceived burdensomeness but not thwarted belongingness. Post hoc multi-group analysis found that this pathway was consistent across Black, Asian, and Latinx groups but was completely mediated for the Asian group. The findings suggest that online racism can increase feelings of being a burden to society, which can trigger thoughts of suicide. This process may be particularly salient among Asian individuals. Implications for future research are discussed.